1987
DOI: 10.1111/j.1600-0773.1987.tb01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Pain Thresholds after the Application of Lypressin, a Vasopressin Analogue

Abstract: Recent animal studies indicate that vasopressin has analgetic properties. The aim of this study was to find out if lypressin, a vasopressin analogue, produces analgesia in man. The effect of i.n. lypressin (5 and 10 I.U.) on experimental pain was tested in healthy humans. The lower dose proved high enough to produce a significant antidiuretic effect. Lypressin did not have any marked analgetic effect at these doses either on ischaemic, cutaneous thermal, or dental pain. The results indicate that lypressin cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…V1AR is believed to predominate in the central nervous system (CNS) 3 and its involvement in affiliation and social communication in microtine rodents 4 and humans 5-6 is known to be male-specific and genetically determined. In humans, two studies using intranasal AVP analogs observed no 7 or modest effects on acute pain 8 . In rodents, AVP produces clear but modest inhibition of acute, thermal pain after systemic, supraspinal or spinal injection in rodents, but most of the evidence suggests that this analgesia is mediated by the V1BR 9 or the V2R 10-11 .…”
Section: Introductionmentioning
confidence: 99%
“…V1AR is believed to predominate in the central nervous system (CNS) 3 and its involvement in affiliation and social communication in microtine rodents 4 and humans 5-6 is known to be male-specific and genetically determined. In humans, two studies using intranasal AVP analogs observed no 7 or modest effects on acute pain 8 . In rodents, AVP produces clear but modest inhibition of acute, thermal pain after systemic, supraspinal or spinal injection in rodents, but most of the evidence suggests that this analgesia is mediated by the V1BR 9 or the V2R 10-11 .…”
Section: Introductionmentioning
confidence: 99%